B-1a B Cells Regulate T Cell Differentiation Associated with Pregnancy Disturbances - Muzzio, Damian O.; Soldati, Rocío; Rolle, Luise; Zygmunt, Marek; Zenclussen, Ana C.; Jensen, Federico (Frontiers in Immunology, 2014)
During pregnancy, the maternal immune system faces a double dilemma: tolerate the growing semi-allogeneic fetus and at the same time protect the mother and the progeny against pathogens. This requires a fine and extremely regulated equilibrium between immune activation and tolerance. As professional antigen presenting cells, B cells and in particular B-1a B cells, can activate or tolerize T cells and thus participate in the generation or regulation of the immune response. B-1a B cells were involved in the humoral immune response leading to pre-eclampsia, one of the main medical complications during pregnancy. Here we demonstrated that B-1a B cells are additionally involved in cellular immune mechanisms associated with pregnancy complications. Using a mouse model of pregnancy disturbances, we showed that B-1a B cells from animals suffering pregnancy disturbances but not from those developing normal pregnancies induce the differentiation of naïve T cells into Th17 and Th1 cells. This differential role of B-1a B cells during pregnancy seems to be associated with the co-stimulatory molecule CD86 as normal pregnant mice showed lower percentages of CD86 expressing B-1a B cells as compared to pregnant mice developing pregnancy disturbances or to non-pregnant animals. Our data bring to light a new and not explored role of B-1a B cells in the context of pregnancy.